Dietary phosphate restriction prevents the appearance of sarcopenia signs in old mice. Issue 2 (28th February 2023) - Alcalde‐Estévez, Elena; Sosa, Patricia; Asenjo‐Bueno, Ana; Plaza, Patricia; Valenzuela, Pedro L.; Naves‐Díaz, Manuel; Olmos, Gemma; López‐Ongil, Susana; Ruiz‐Torres, María P.
Abstract: Background: Sarcopenia is defined by the progressive and generalized loss of muscle mass and function associated with aging. We have previously proposed that aging‐related hyperphosphataemia is linked with the appearance of sarcopenia signs. Because there are not effective treatments to prevent sarcopenia, except for resistance exercise, we propose here to analyse whether the dietary restriction of phosphate could be a useful strategy to improve muscle function and structure in an animal model of aging. Methods: Five‐month‐old (young), 24‐month‐old (old) and 28‐month‐old (geriatric) male C57BL6 mice were used. Old and geriatric mice were divided into two groups, one fed with a standard diet (0.6% phosphate) and the other fed with a low‐phosphate (low‐P) diet (0.2% phosphate) for 3 or 7 months, respectively. A phosphate binder, Velphoro®, was also supplemented in a group of old mice, mixed with a standard milled diet for 3 months. Muscle mass was measured by the weight of gastrocnemius and tibial muscles, and quality by nuclear magnetic resonance imaging (NMRI) and histological staining assays. Muscle strength was measured by grip test and contractile properties of the tibialis muscle by electrical stimulation of the common peroneal nerve. Gait parameters were analysed during the spontaneous locomotion of the mice with footprinting. Orientation and motor coordination were evaluated using a static rod test. Results: Old mice fed with low‐P diet showed reduced serum phosphate concentration (16.46 ± 0.77 mg/dL young; 21.24 ± 0.95 mg/dL old; 17.46 ± 0.82 mg/dL low‐P diet). Old mice fed with low‐P diet displayed 44% more mass in gastrocnemius muscles with respect to old mice ( P = 0.004). NMRI revealed a significant reduction in T2 relaxation time ( P = 0.014) and increased magnetization transfer ( P = 0.045) and mean diffusivity ( P = 0.045) in low‐P diet‐treated mice compared with their coetaneous. The hypophosphataemic diet increased the fibre size and reduced the fibrotic area by 52% in gastrocnemius muscle with respect to old mice ( P = 0.002). Twitch force and tetanic force were significantly increased in old mice fed with the hypophosphataemic diet ( P = 0.004 and P = 0.014, respectively). Physical performance was also improved, increasing gait speed by 30% ( P = 0.032) and reducing transition time in the static rod by 55% ( P = 0.012). Similar results were found when diet was supplemented with Velphoro®. Conclusions: The dietary restriction of phosphate in old mice improves muscle quantity and quality, muscle strength and physical performance. Similar results were found using the phosphate binder Velphoro®, supporting the role of phosphate in the impairment of muscle structure and function that occurs during aging.